2013
DOI: 10.31274/ans_air-180814-1055
|View full text |Cite
|
Sign up to set email alerts
|

Feed Intake and Growth Rate in Purebred Berkshire Pigs Housed in Hoop Buildings in Iowa

Abstract: and Implications Niche marketing continues to grow in Iowa and the United States as the demand for high quality pork increases for both in home and out of home consumption. The majority of pigs in demand for these markets are Berkshires, with many raised in bedded hoop barns. Berkshires have been shown to have significant advantages in meat eating quality, with significantly poorer feed conversion and higher feed costs. However very little information exists as to how these pigs grow and the nutritional needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A similar study conducted by Swantek et al [7] reported the feed intake and growth rate of purebred Berkshire pigs housed in hoop buildings in Iowa. Growth performance measurements were reported in terms of initial weight, final weight, and average daily gain (ADG).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A similar study conducted by Swantek et al [7] reported the feed intake and growth rate of purebred Berkshire pigs housed in hoop buildings in Iowa. Growth performance measurements were reported in terms of initial weight, final weight, and average daily gain (ADG).…”
Section: Introductionmentioning
confidence: 89%
“…Very few studies have been conducted that involve performance tests of purebred Berkshire pigs raised outdoors, due to the difficulties in measuring body weight (BW) and feed intake outdoors. A similar study conducted by Swantek et al [ 7 ] reported the feed intake and growth rate of purebred Berkshire pigs housed in hoop buildings in Iowa. Growth performance measurements were reported in terms of initial weight, final weight, and average daily gain (ADG).…”
Section: Introductionmentioning
confidence: 89%
“…Recent studies on farrowing performances of Berkshire sows have been reported in Japan by Tomiyama et al (2008), Sasaki et al (2014) and Usui and Koketsu (2015). A study was conducted in Iowa that reported the feed intake and growth rate of purebred Berkshire pigs housed in hoop buildings in terms of initial weight, final weight, ADG and feed-to-gain ratio (Swantek et al 2013). However, body measurement records and factors affecting their relative growth have not been reported specifically on purebred Berkshire pigs in the United States.…”
Section: Introductionmentioning
confidence: 99%